Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G; Abreu, José M F (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use